Trusting the Influencer: How Brand Credibility Shapes Buying Behavior - Reni Yesi S; Irdawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
This study investigates the influence of influencer marketing on consumer purchase decisions, with brand trust serving as a mediating variable. With the growing reliance on social media platforms for brand communication, understanding the mechanisms behind consumer behaviour has become increasingly important. A quantitative approach was employed using data from 250 respondents in Indonesia, analysed through Structural Equation Modelling with Smart-PLS. The results reveal that influencer marketing does not directly affect purchase decisions. However, it has a significant positive impact on brand trust, which in turn strongly influences purchase behaviour. Furthermore, brand trust is proven to mediate the relationship between influencer marketing and purchase decisions effectively. These findings emphasize that trust in the endorsed brand plays a pivotal role in converting influencer exposure into actual purchasing actions. The study provides valuable insights for marketers seeking to enhance the effectiveness of influencer campaigns by focusing on strategies that build consumer trust. It also contributes to the growing body of digital marketing literature by clarifying the indirect pathway through which influencer marketing shapes consumer intentions. Future research is encouraged to explore other mediating or moderating variables and to examine the model in broader cultural contexts.